The Prologue to the Greek Crisis - Renate Neubäumer (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
This paper analyzes the prologue to the Greek tragedy-in particular, the long period of slow growth after Greece joined the European Union and the short period of very strong growth following its adoption of the euro-and deduces reform proposals. Ultimately, a growth strategy should contain three interrelated bundles of measures: First, an improvement of the institutional environment, which currently makes it difficult to do business in Greece and thus leads to too little investment. Second, a reorganization of public finances and the creation of a leaner, more efficient administration, as well as a reform of the pensions system. Third, an expansion of the industrial basis and the modern sector in order to build a strong export basis. All of these measures entail comprehensive changes to Greece's economy and Greek society, and the majority of Greeks must therefore be in favor of them. The alternative is to opt for moderate reforms and to return to the old path of low growth and a lower living standard.
Keywords: O52; E02; 330; Greece; slow growth; growth strategy; economic measures